Violence against women in the 21st Century: unveiling history (Research, Society and Development, 2022)
The themes about violence against women are old, however, timeless, since they are still very present in 21st century society. The origin of this violence cannot be measured, therefore it does not come from a specific time, culture, social class or specific location. In this perspective, the present work sought to analyze the 21st century Woman approach and the duality of female violence. In view of this, articles present in platforms such as the Portal of Electronic Journals in Psychology (PePSIC); Scientific Electronic Library Oline (SciELO); CAPES Portal and Brazilian Digital Library of Theses and Dissertations (BDTD), in addition to federal platforms for the systematization of knowledge of the laws in force in the country. The works analyzed here were understood during the period 2015-2022, being used as main descriptors Violence against women and Coping with violence. The present study aimed to discuss the woman of the 21st century and the duality of female violence. Thus, it was found that the woman of the 21st century evolved thanks to her impetus and determination, but she still finds herself hostage to a violence that has very deep social roots and with a process of deconstruction that is very difficult to project. Thus, it was evident in the study that the basic rights of women are still not respected in their entirety, putting the woman in front of a feeling of deep devaluation, fear and insecurity.